2022
DOI: 10.3390/brainsci12070858
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Model of Hemorrhage Transformation in Patient with Acute Ischemic Stroke Based on Multiparametric MRI Radiomics and Machine Learning

Abstract: Intravenous thrombolysis is the most commonly used drug therapy for patients with acute ischemic stroke, which is often accompanied by complications of intracerebral hemorrhage transformation (HT). This study proposed to build a reliable model for pretreatment prediction of HT. Specifically, 5400 radiomics features were extracted from 20 regions of interest (ROIs) of multiparametric MRI images of 71 patients. Furthermore, a minimal set of all-relevant features were selected by LASSO from all ROIs and used to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 37 publications
(42 reference statements)
0
6
0
Order By: Relevance
“… 43 To predict hemorrhage transformation, Meng et al. 44 introduced a multifaceted MRI radiomics-based model coupled with machine learning. Four distinct predictive models were cultivated within a primary training cohort and subsequently validated using an independent dataset.…”
Section: Application Of Imaging Radiomics In Ischemic Cerebrovascular...mentioning
confidence: 99%
“… 43 To predict hemorrhage transformation, Meng et al. 44 introduced a multifaceted MRI radiomics-based model coupled with machine learning. Four distinct predictive models were cultivated within a primary training cohort and subsequently validated using an independent dataset.…”
Section: Application Of Imaging Radiomics In Ischemic Cerebrovascular...mentioning
confidence: 99%
“…Another approach for predicting ICH after thrombolysis combined MRI radiomics from different regions of interest using different parametric maps with clinical data into a random forest model, which achieved an improved area under the curve of 0.91. 73 The drawback of this approach is the time-consuming aspect of feature extraction from manually selected regions and the use of a single vendor's software for producing the parametric maps. Yu et al 74 investigated different machine learning models in patients treated with thrombolysis or EVT using pretreatment diffusion-weighted imaging and raw MRI perfusion imaging to predict the voxel-wise ICH probability.…”
Section: Artificial Intelligencementioning
confidence: 99%
“…A recent study exploring MRI and machine learning prediction models for predicting HT in AIS patients has shown that combining clinical variables, such as blood pressure and glucose, with radiomics features improved the prediction performance [91]. A logical next step for future research could be to establish a more individualized, precise, and stable multi-parameter diagnostic model for predicting HT with different etiologies, infarct sites, treatment approaches, treatment outcomes, and other factors.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%